The Use of Magnetic Resonance Imaging to Predict Placenta Previa With Placenta Accreta Spectrum. Issue 3 (25th September 2021) - Ishibashi, H.; Miyamoto, M.; Shinmoto, H.; Soga, S.; Matsuura, H.; Kakimoto, S.; Iwahashi, H.; Sakamoto, T.; Hada, T.; Suzuki, R.; Takano, M.
Abstract : ( Acta Obstet Gynecol Scand . 2020;99:1657–1665) Placenta previa with placenta accrete spectrum (PAS) affects an increasing number of pregnancies and is associated with risk for massive hemorrhage and maternal morbidity. Recently, studies have examined the use of magnetic resonance imaging (MRI) to predict placenta previa with PAS. Some studies have found high specificity and sensitivity using certain MRI findings to make this prediction, while others have found this tool less useful. The aim of this study was to examine the diagnostic accuracy of MRI findings to predict posterior and anterior placenta previa with PAS.